Critical thinking and reading comprehension in a course of English as a foreign language - Fernández de Morgado, Nelly Yiveline; Mayora Pernía, Carlos Alberto; St. Louis, Rubena (Íkala, Revista de Lenguaje y Cultura, 2015)
There is great interest in designing English-as-a-foreign-language learning environments to foster critical thinking. In order to do so, understanding the nature of the relationships between the elements involved is necessary. In this sense, the present study aims at determining the relationship between critical thinking abilities (CTA) and reading comprehension (RC) of scientific technical texts in students of English as a foreign language at Universidad Simón Bolívar, Venezuela. This is a transverse exploratory after-the-fact field research framed in a quantitative approach using correlations. The Ennis-Weir Critical Thinking Essay Test was used to measure critical thinking abilities and the De-partmental Reading Comprehension Achievement Test was used to measure linguistic competence. Results show that the relationship between CTA andRC is low, positive and significant. Also, both CTA as well as RC scores were very low. Findings suggest that reading is a useful tool to foster CTA; nonetheless, the course must be tailored in order to improve its effectiveness. Pedagogical implications are discussed. Also, future research suggestions are offered.